Analysis of the Use of Google Forms in the Assessment Process of Distance Learning at SMP Rahmat Islamiyah Medan - Hasrian Rudi Setiawan; Muhammad Syukri Maulana (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to analyze the use of Google Forms as an evaluation medium in the assessment process of distance learning at SMP Rahmat Islamiyah Medan. The research method used is descriptive qualitative with data collection techniques including observation, interviews, and documentation. The results indicate that Google Forms provides convenience for teachers in creating, distributing, and correcting evaluation questions efficiently. Additionally, students responded positively as they could easily access exam questions through digital devices. Although there were some obstacles such as unstable internet connections and limited device availability, overall the use of Google Forms improved the effectiveness and efficiency of the distance learning assessment process. This study recommends ongoing training for teachers and improvement of digital facilities to support technology-based learning.